Integrasi Nilai – Nilai Islam dalam Pembentukan Karakter Gen Z: Penelitian - Evi Febriani; Muhamad Kumaidi; Annisa Septiana; Anisa Fadila; Anisa, Anisa; Alfina Damayanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article discusses the integration of Islamic values ​​in the character development of Generation Z. Currently, Generation Z is faced with various influences that have the potential to shape their character amidst globalization, technological advances, and unlimited access to information. Generation Z was born between 1997 and 2012. Islamic values ​​play a crucial role in shaping Generation Z's character, helping them overcome challenges in the digital era, such as cyberbullying and the spread of hoaxes. This study aims to examine how Islamic values ​​can be effectively integrated into the character development process of Generation Z. With these values, Generation Z can avoid negative influences resulting from technological developments. This study uses a qualitative approach using a literature study method. This study identified various relevant literature sources, including books, journal articles, and official documents, to collect data. The research findings show that Islamic values ​​provide strong moral guidance in facing ethical challenges in the digital and pluralistic era. This helps shape a strong and stable character in Generation Z.